Determination of Measurement Points in Urban Environments for Assessment of Maximum Exposure to EMF Associated with a Base Station - Agostinho Linhares; Antonio José Martins Soares; Marco Antonio Brasil Terada (International Journal of Antennas and Propagation)
A base station (BS) antenna operates in accordance with the established exposure limits if the values of electromagnetic fields (EMF) measured in points of maximum exposure are below these limits. In the case of BS in open areas, the maximum exposure to EMF probably occurs in the antenna’s boresight direction, from a few tens to a few hundred meters away. This is not a typical scenery for urban environments. However, in the line of sight (LOS) situation, the region of maximum exposure can still be analytically estimated with good results. This paper presents a methodology for the choice of measurement points in urban areas in order to assess compliance with the limits for exposure to EMF.